TRACER STUDY FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - DARMA RIKA; ACHMAD FAUZI; HENRY ERYANTO; R.R.PONCO DEWI (Fakultas Ekonomi Universitas Negeri Jakarta, 2014)
Abstract This study was conducted to identify the competencies of graduates FE UNJ waiting times based upon the profile of the work , the suitability of the first areas of work, salary and perceptions about the competence of the alumni corporation. This research is a qualitative study and the population are alumnies of the Faculty of Economics who working in government agencies, private and entrepreneur and graduated from the period 2011/2012 to 2012/2013. Sample of the population is set at 10 % of the total population, and using a technique comvenience sampling ( non probability sampling ). The data used in this study is primary data obtained from interviews and use the questionnaire instrument. Data were analyzed using descriptive statistics by looking at the frequency distribution and the average of respondents’s answers regarding the competence of graduates of the Faculty of Economics UNJ. 92.8% of alumni of the Faculty of Economics working as employees of the company, 5.8 % be a teacher, others go to college and as entrepreneurs . The average waiting time for alumnies FE UNJ only takes waited less than 6 months to get a job. The level of salary received at the time of the first alumni of work varies with an average of 2-3 million by 49 % and between 3 million and above by 23 % . The level of compliance competencies and job average amounted to 77 % of alumni and competence of alumni based on the user 's perception was expressed by 71 % of alumni FE UNJ have a good competence. Keywords: competencies, profile, Faculty of Economic